2013
DOI: 10.5897/sre12.554
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the productivity of soil amended with different animal wastes in an acid ultisol at Abakaliki, Southeast Nigeria

Abstract: The result indicated that bulk density, total porosity, aggregate stability, mean weight diameter and state of aggregation were significantly (P < 0.05) higher in poultry droppings amended plots compared to control. Soil pH, total N, Calcium, Potassium, Sodium, effective cation exchange capacity, percent base saturation and exchangeable acidity were significantly (P < 0.05) higher in plots amended with poultry droppings when compared to control. Plots amended with poultry droppings gave the highest grain yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
3
3
0
Order By: Relevance
“…This corroborates the findings of Nwite (2013) that individual productivity indicators influenced productivity index in predictions. Significantly higher correlation coefficient obtained between the individual productivity indicator and calculated productivity index tends to suggest that there was synergy among the productivity indicators in promoting prediction of grain yields of maize.…”
Section: Discussionsupporting
confidence: 91%
“…This corroborates the findings of Nwite (2013) that individual productivity indicators influenced productivity index in predictions. Significantly higher correlation coefficient obtained between the individual productivity indicator and calculated productivity index tends to suggest that there was synergy among the productivity indicators in promoting prediction of grain yields of maize.…”
Section: Discussionsupporting
confidence: 91%
“…These data suggest that differences in crop yield can be represented by productivity indices values. This finding agreed with [3] and [39] who found that corn yield increased with the increase of PI and decreased with the decrease of it. The results concluded that as PI, PIm and RI values decreased a general decline in grain yield of rice is recorded.…”
Section: Individual Productivity Index and Grain Yield Of Ricesupporting
confidence: 93%
“…Floodplains have reported to be fragile ecosystems and their conversion to cropland may result in severe ecological and environmental deterioration and degradation if not appropriately done [1]. However, increasing demand for food as a result of rapid population expansion in Nigeria necessitates a substantial extension of croplands into some hitherto uncultivated wetlands/floodplains otherwise considered as marginal lands for rain-fed agriculture [2,3]. Basic soil resource information a pre-requisite for planning sustainable agriculture [4,1] and sustainable agriculture requires both direct and indirect knowledge of the capability and nutrient status of the soils to be utilized [5].…”
Section: Introductionmentioning
confidence: 99%
“…Promoting the application of the cattle manure currently being used as fuel for cooking to the fields seems to be a feasible strategy. Application of manure improves physical and chemical properties of soils (Nwite et al 2013;Okenmuo et al 2018). However, a study by Corral-Nunez et al (2014) in the same area reported that applying manure alone is not sufficient to off-set the declining trend, due to limited availability and its various alternative uses.…”
Section: Full Nutrient Balance At Field Levelmentioning
confidence: 99%